INDONESIA – AMERIKA DALAM KERANGKA COMPRHENSIVE PARTNERSHIP - Yerichielli Yerichielli (Global Political Studies Journal, 2019)
Indonesian political and strategic relations are quite good with the United States, especially since the New Order regime in Indonesia, namely in the 1960s. But economic ties the two sides have not grown enough in comparison with the United States economic relations with neighboring Indonesia, Singapore and Australia. In terms of political and strategic aspects in the relationship between the two countries produced in the United States and Indonesia are less developed the economic potential between the two. Both countries have significant potential to further enhance the bilateral relations to the mutual interest through the establishment of a comprehensive partnership (Comprehensive Partnership) is a strategic step in improving relations of cooperation in politics, economy, security, environment, energy, education and other areas of life other. Efforts to improve relations between the two sides appeared in recent years because of the encouragement of the government of Indonesia and US efforts to seek larger markets in order to restore its economic crisis. In November 2010 the leaders of both countries signed the US-Indonesia Compherensive Partnership Agreement (US-Indonesia CPA) which is a long-term commitment of both countries to enhance and deepen bilateral relations. One sector that is the focus of the cooperation is the economic sector.